2000
DOI: 10.1038/oby.2000.57
|View full text |Cite
|
Sign up to set email alerts
|

Obesity Management: Australian General Practitioners’ Attitudes and Practices

Abstract: Objectives: To document general practitioners’ (GPs) attitudes and practices regarding the prevention and management of overweight and obesity. Research Methods and Procedures: A cross‐sectional survey of a randomly selected sample of 1500 Australian GPs was conducted, of which 752 questionnaires were returned. The measures included views on weight management, definitions of success, views regarding the usefulness of drugs, approaches to and strategies recommended for weight management, and problems and frustr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

14
120
3
5

Year Published

2002
2002
2014
2014

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 145 publications
(142 citation statements)
references
References 16 publications
14
120
3
5
Order By: Relevance
“…They had a greater sense of professional satisfaction than practitioners in other countries (11) , probably because they set realistic weightloss goals. Despite this, they have judged their weightmanagement practice as ineffective.…”
Section: Resultsmentioning
confidence: 99%
“…They had a greater sense of professional satisfaction than practitioners in other countries (11) , probably because they set realistic weightloss goals. Despite this, they have judged their weightmanagement practice as ineffective.…”
Section: Resultsmentioning
confidence: 99%
“…Similar results were found in other studies. 13,15 Although FPs are potentially wellplaced to play a key role in the prevention and management of obesity, there are several factors that limit medical practitioners' capacity to deliver such interventions. An Israeli survey among persons aged 45 -75 who visited their FP in the last 3 months found that only 16% perceived that they were given advice regarding physical activity and weight reduction.…”
Section: Discussionmentioning
confidence: 99%
“…11 FPs' awareness of and diagnosis of the obese and overweight is low and may contribute to its undermanagement. 12 There is also reluctance to treat patients without comorbidities, 13 as there is to treat the overweight, as opposed to the obese. 14 In an era of rapidly growing prevalence of obesity and the newly introduced anti-obesity medications, it is important to explore the current attitudes and practices of primary care physicians, particularly among non-specialists, specialists and residents in family practice.…”
Section: Introductionmentioning
confidence: 99%
“…GPs and primary care nurses (PCNs) believe weight management is part of their role, but perceive their effectiveness as poor (Campbell et al, 2000;Counterweight Project Team, 2004a). Foster et al (2003) found that the treatment of obesity was rated as significantly less effective than therapies for nine out 10 chronic diseases.…”
Section: Introductionmentioning
confidence: 99%